Accidents with venomous and poisonous animals: their impact on occupational health in Colombia - Juan P. Gómez C (Universidad de Antioquia, 2011)
Venomous or poisonous animals are a very common cause of accidents in Colombia. Such accidents occur due to vertebrates such as snakes and fish or invertebrates such as scorpions, spiders, bees, etc. The most affected individuals are young people ages 15 to 45. They are mainly farmers and fishermen. These events can be considered work accidents given their characteristics. Nevertheless, the occupational risk insurance companies, the central Colombian government, and the regional, departmental, and municipal governmental authorities do not record or study these events. Therefore, the true magnitude of the problems caused by this, and the social, economic and occupational losses for Colombia and its companies are not perceived. Likewise, Colombian companies lack protocols, manuals, mechanisms for the identification of potentially dangerous animals to which workers are exposed based on their sector or occupation. This critical factor can have direct implications in the treatments applied to specific cases. This review article attempts to contextualize the impact of poisonous and venomous animals on the health of workers by presenting theoretical foundations and concepts for approaching this issue.